Soil management with winter cover crops - Derpsch, Rolf; Sidiras, Nikolaos; Heinzmann, Franz X. (Pesquisa Agropecuaria Brasileira, 2014)
Field experiments were conducted to study the effects of white lupine (Lupinus albus), broad beans (Vicia villosa), lathyrus (Lathyrus sativus), rye (Secale cereale), black oats (Avena strigosa), wheat (Triticum aestivum), fodder radish (Raphanus sativus), rapeseed (Brassica napus), and sunflower (Helianthus annuus) on soil temperature, moisture regime and yields of corn (Zea mays), soybeans (Glycine max), and beans (Phaseolus vulgaris) under no-tillage. The highest moisture contents were measured on the plots with black oats and lowest with lathyrus and fodder radish. The maximum soil temperature was obtained on bare plots and the minimum on plots with black oats. Corn, soybeans and beans grain yields were found to be dependent on the winter cover crop species. The highest corn yields were obtained after white lupine, soybeans after black oats, and beans after fodder radish, respectively.